2021
DOI: 10.3390/molecules26133827
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Therapeutic and Nutraceutical Applications of p-Methoxycinnamic Acid from Plant Origin

Abstract: The p-methoxycinnamic acid (p-MCA) is one of the most studied phenylpropanoids with high importance not only in the wide spectrum of therapeutic activities but also its potential application for the food industry. This natural compound derived from plants exhibits a wide range of biologically useful properties; therefore, during the last two decades it has been extensively tested for therapeutic and nutraceutical applications. This article presents the natural sources of p-MCA, its metabolism, pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Table 3 shows the comparison of identified compounds with previous studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ,…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the comparison of identified compounds with previous studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ,…”
Section: Resultsmentioning
confidence: 99%
“…Cinnamic acid is a natural compound found in various plants and spices. 152 Piperazine is a moiety found in many approved drugs and is widely used as a linker for designing of novel compounds. 153 A series of 8HQ-cinnamic acid with piperazine linker were developed as multifunctional compounds.…”
Section: Figure 6 8hq-based and 8hq-inspired Copper Chelators As Anti...mentioning
confidence: 99%
“…This indicated that the compound p-methoxy cinnamic acid could act as an excellent sunscreen agent. P-methoxy cinnamic acid has a chromophore group, which is a conjugated double bond in its aromatic ring, aliphatic C=C, a C=O group, and an auxochrome group from OCH3 [1] so that it can absorb UV B rays and can be used as an active sunscreen agent with excellent potential [22][23].…”
Section: Sunscreen Activitymentioning
confidence: 99%
“…P-methoxy cinnamic acid is one of the cinnamic acid derivative compounds substituted for a methoxy group at the para position [1]. The compound p-methoxy cinnamic acid has activity as an antibacterial [2][3], an anti-inflammatory and anticancer [4], antioxidant, antidiabetic [5], hepatoprotective, neuroprotective, and chemopreventive activity [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation